Market integration, the Specialization of Production and Labour Mobility Under Endogenous Differentiation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
This paper shows that market integration has controversial effects when countries are not similar in terms of income but may significantrìly differ in terms of consumer tastes and the cost of labour. The long run adjustments observed in the specialization of production (or product differentiation) and prices interact in non trivial ways with labour mobility (and the associated adjustment in the wage differential) to determine the relative performance of rirms (as for equilibrium profits) and countries (as for equilibrium social welfare). It iis shown that there are interesting cases where the welfare enjoyed by the larger country is smaller than the smaller counties', due to relative distribution of demand and labour.
Keywords: 330